2022
DOI: 10.3390/su14031186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Producer’s Environmental Performance on Consumers and Retailers Simultaneously in the Indonesian Retail Environment

Abstract: Producers improve environmental performance to reduce the release of post-production waste. The positive environmental performance of producers is expected to influence consumer environmental attitudes positively, specifically toward post-consumption waste. However, research is deficient in exploring the impact of producer environmental performance (PEP) on retailer-consumer relationship quality (RCRQ) and consumer purchasing behavior (CPB) simultaneously to drive consumer environmental attitude (CEA) in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
2
1
0
Order By: Relevance
“…Even though the combination of these research variables was not tested previously, especially in airports, the results are consistent with Fajar et al . (2022) study, as the results demonstrated that environmental performance significantly affects lubricant producers' purchasing behavior in the Indonesian industrial city of Gresik (Fajar et al ., 2022). Moreover, increasing EK will positively impact ATT as gaining more knowledge would necessarily change the mindset of individuals in NAC toward reasonable environmental practices.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Even though the combination of these research variables was not tested previously, especially in airports, the results are consistent with Fajar et al . (2022) study, as the results demonstrated that environmental performance significantly affects lubricant producers' purchasing behavior in the Indonesian industrial city of Gresik (Fajar et al ., 2022). Moreover, increasing EK will positively impact ATT as gaining more knowledge would necessarily change the mindset of individuals in NAC toward reasonable environmental practices.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, based on the findings of this research, it can be argued that EP affects the ATT of passengers, which means that better sustainability performance for the organizations could lead to better sustainability performance for all stockholders’ supply chains and achieve better EB (Afzal and Lim, 2022; Yun et al ., 2018). Even though the combination of these research variables was not tested previously, especially in airports, the results are consistent with Fajar et al . (2022) study, as the results demonstrated that environmental performance significantly affects lubricant producers' purchasing behavior in the Indonesian industrial city of Gresik (Fajar et al ., 2022).…”
Section: Discussionsupporting
confidence: 86%
“…However, the view of the Indonesian people about green products that are considered expensive and the availability of products that are not too many are factors that consumers choose non-green products (Tarigan et al, 2020). In this case, people in developing countries such as Indonesia have not fully consistent green consumption patterns over time (Anggraeni & Balqiah, 2021;Fajar et al, 2022;Fibrianto et al, 2021;Hutahaean & Kurnia, 2021). That is, there is a gap between attitudes and behavior, which indicates that the positive attitude of consumers towards the product is not necessarily actualized in the act of purchase.…”
Section: Introductionmentioning
confidence: 99%